2003
DOI: 10.1137/s0036141001392815
|View full text |Cite
|
Sign up to set email alerts
|

Robust Permanence for Ecological Differential Equations, Minimax, and Discretizations

Abstract: We present a sufficient condition for robust permanence of ecological (or Kolmogorov) differential equations based on average Liapunov functions. Via the minimax theorem we rederive Schreiber's sufficient condition [S. Schreiber, J. Differential Equations, 162 (2000), pp. 400-426] in terms of Liapunov exponents and give various generalizations. Then we study robustness of permanence criteria against discretizations with fixed and variable stepsizes. Applications to mathematical ecology and evolutionary games a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 54 publications
4
95
0
1
Order By: Relevance
“…They showed that for certain systems persistence holds even when one has small perturbations of the growth functions. There have been results on robust persistence in the deterministic setting for Kolmogorov systems by Schreiber (2000) and Garay and Hofbauer (2003). Recently, robust permanence for deterministic Kolmogorov equations with respect to perturbations in both the growth functions and the feedback dynamics has been analyzed by Patel and Schreiber (2016).…”
Section: Discussion and Generalizationsmentioning
confidence: 99%
“…They showed that for certain systems persistence holds even when one has small perturbations of the growth functions. There have been results on robust persistence in the deterministic setting for Kolmogorov systems by Schreiber (2000) and Garay and Hofbauer (2003). Recently, robust permanence for deterministic Kolmogorov equations with respect to perturbations in both the growth functions and the feedback dynamics has been analyzed by Patel and Schreiber (2016).…”
Section: Discussion and Generalizationsmentioning
confidence: 99%
“…The papers by Faria and Röst [12], Freedman and Ruan [15], Garay and Hofbauer [16], Hetzer and Shen [20], Hirsch et al [21], Langa et al [26], Magal and Zhao [28], Mierczyński and Shen [30], Mierczyński et al [31], Novo et al [36], Salceanu and Smith [43], Schreiber [44,45], Thieme [51,52], Wang and Zhao [54], and references therein, provide a long but not complete list of works on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling is especially useful for exploring these idealized scenarios. Furthermore, permanence, or persistence in mathematical models is known to be robust to model perturbations under appropriate conditions [10,3,5] and therefore it should continue to hold for small deviations from a nested infection structure.…”
mentioning
confidence: 99%